A case of neurosarcoidosis secondary to treatment of etanercept and review of the literature. (6th July 2015) - Berrios, Idanis; Jun-O'Connell, Adalia; Ghiran, Sorina; Ionete, Carolina
Abstract : There are only three cases in the literature that describe development of neurosarcoidosis in a patient who is on tumour necrosis factor α inhibitors. We describe a case of a 33-year-old woman with a history of juvenile rheumatoid arthritis and refractory uveitis (with previous treatment trials of adalimumab, infliximab, mycophenolate, methotrexate) who had been stable for 2 years on etanercept. She was diagnosed with biopsy-proven systemic sarcoidosis with meningeal and parenchymal neurosarcoidosis. She was switched to infliximab and methotrexate, with clinical and imaging improvements. This is a case that demonstrates the difficulty of choosing tumour necrosis factor α (TNF-α) inhibitors when treating patients with multiple clinical autoimmune entities. It is also a case where a change in the mechanism of TNF-α inhibition pathway can still be used to treat refractory sarcoidoisis and rheumatoid arthritis. It is still unclear what the exact difference between the TNF-α blockers and their neurological complications is, and who the patients at risk of developing neurological complications are.